Pre-Service Teachers’ Views on Stem-Based Environmental Education With Arduino Materials - Koçak, Edanur; Yalçın-Çelik, Ayşe; Uluyol, Çelebi (Research Trends In Educational Sciences, 2025)
Digital technologies have started to be widely used in the classroom.  For this reason, it was important to determine the views of teachers, who play an important role in the integration of technology, on these digital tools and devices. The aim of study was to have pre-service science teachers design materials that can be used to take measurements with digital sensor sets in activities based on the STEM approach, and to determine the pre-service teachers' views on the preparation process of these materials. The sample of the study consisted of 31 pre-service teachers studying in biology, science and chemistry education departments of a state university. The participants experienced digital sensors in a course where environmental education was taught with activities based on the STEM approach. According to the results of the research, the participants stated that the use of digital sensors in the classroom was appropriate to increase students' digital literacy and effective in terms of attracting students' attention and supporting their design development. Participants believe digital technology benefits creativity, interest and learning. However, they also see disadvantages in sensors, training and cost. sensors can deteriorate quickly, that training is needed to use them, and that they are expensive.